Anabolic steroids abuse and male infertility. Issue 1 (December 2016) - El Osta, Rabih; Almont, Thierry; Diligent, Catherine; Hubert, Nicolas; Eschwège, Pascal; Hubert, Jacques
Abstract For several decades, testosterone and its synthetic derivatives have been used with anabolic and androgenic purposes. These substances were first restricted to professional bodybuilders, but become more and more popular among recreational athletes. Up to date, 3, 000, 000 anabolic-androgenic steroids (AAS) users have been reported in the United States with an increasing prevalence, making AAS consumption a major public health growing concern. Infertility is defined by the WHO as the failure to achieve a clinical pregnancy after 12 months or more of regular unprotected sexual intercourse and a male factor is present in up to 50 % of all infertile couples. Several conditions may be related to male infertility. Substance abuse, including AAS, is commonly associated to transient or persistent impairment on male reproductive function, through different pathways. Herein, a brief overview on AAS is offered. Steroids biochemistry, patterns of use, physiological and clinical issues are enlightened. A further review about fertility outcomes among male AAS abusers is also presented, including the classic reports on transient anabolic steroid-induced hypogonadism (ASIH), and the more recent experimental reports on structural and genetic sperm damage. Resume Depuis plusieurs décennies, la testostérone et ses dérivés synthétiques ont été utilisés à des fins anaboliques et androgéniques. Initialement réservées aux culturistes professionnels, ces substances ont été progressivement utilisées par les athlètes et les pratiquants de la musculation. Actuellement, pas moins de 3 millions d'utilisateurs de stéroïdes anabolisants ont été signalés aux États-Unis, et la prévalence croissante de cette utilisation fait de ce phénomène un sujet de préoccupation majeur. L'infertilité est définie comme l'incapacité à obtenir une grossesse réussie après 12 mois ou plus de rapports sexuels réguliers non protégés, le facteur masculin étant impliqué dans 30 à 50 % des cas parmi tous les couples infertiles. L'abus de substances, y compris les anabolisants, est souvent associé à une altération transitoire ou persistante sur la fonction reproductive mâle par différentes voies. Un aperçu des produits anabolisants couramment utilisés ainsi que leurs modes d'utilisation et mécanismes d'action sont présentés. Les implications sur la fertilité sont détaillées. Outre l'inhibition axiale transitoire, les dommages structurels et génétiques des spermatozoïdes, connus à ce jour, sont décrits. Enfin, la spécificité et les modalités de la prise en charge thérapeutique de cette catégorie de patients infertiles sont évoquées.